2020
DOI: 10.1021/acs.macromol.0c01141
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Containing Poly(ionic liquid) Exhibiting Photogeneration of Coordination Network: Reversible Control of Viscoelasticity and Ionic Conductivity

Abstract: The control of physical properties of soft matters via external stimuli is useful for various applications. Poly(ionic liquid)s are versatile liquid polymers exhibiting ionic conductivity, though the development of photoresponsive poly(ionic liquid)s is still limited.Here we report the synthesis and properties of a photoreactive poly(ionic liquid) 1a consisting of a Ru sandwich complex [Ru(C5H5){C6H3(OC6H12CN)3}] + and a polymeric anion -[-CH2-CH(SO2N − SO2CF3)-]n-. Upon UV photoirradiation, the liquid transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Another Ruc o n t a i n i n g p o l y ( i o n i c l i q u i d ) , [ R u ( C 5 H 5 ) -[C 6 H 3 (OC 6 H 12 CN) 3 ]] + , and a polymeric anion, [CH 2 − CH(SO 2 N−SO 2 CF 3 )] n , undergo a UV-induced phase transition. 175 UV irradiation initiates the photochemical reaction of the cation, resulting in a cationic coordination network and anionic covalent chains (T g = −8 °C). In addition to the synthesis of ionic liquids, the formation of 2D and 3D crystalline anionic CPs containing organometallics and ionic liquids has been demonstrated.…”
Section: Direct Synthesis Glassesmentioning
confidence: 99%
“…Another Ruc o n t a i n i n g p o l y ( i o n i c l i q u i d ) , [ R u ( C 5 H 5 ) -[C 6 H 3 (OC 6 H 12 CN) 3 ]] + , and a polymeric anion, [CH 2 − CH(SO 2 N−SO 2 CF 3 )] n , undergo a UV-induced phase transition. 175 UV irradiation initiates the photochemical reaction of the cation, resulting in a cationic coordination network and anionic covalent chains (T g = −8 °C). In addition to the synthesis of ionic liquids, the formation of 2D and 3D crystalline anionic CPs containing organometallics and ionic liquids has been demonstrated.…”
Section: Direct Synthesis Glassesmentioning
confidence: 99%
“…47,48 We previously developed several photoreactive ILs using this mechanism. [49][50][51][52][53] As shown in Fig. 1c, after the addition of a small amount of 1-X, various ILs transformed to ionogels upon UV irradiation.…”
Section: Introductionmentioning
confidence: 91%
“…The ability to remotely modulate ion and/or charge transport using light not only is essential for neurological activity in nature but also enables the fabrication of multifunctional smart materials including photoswitchable organic light-emitting transistors, supramolecular hydrogels, metal organic frameworks, and semiconductors . By introducing light-responsive functional groups into these materials, the optical and/or electrical properties can be noninvasively tuned with excellent spatial and temporal resolution, making them pivotal components for emerging optoelectronics applications such as smart displays, photodetectors, and logic circuits. , Among these materials, polymer electrolytes are an attractive platform due to their high ionic conductivity, tunable polymeric scaffold, and robust mechanical properties. , Importantly, ion mobility and conductivity in these materials are highly dependent on different types of weak interactions, such as cation–anion, polymer–ion, and Lewis acid–base interactions. , The rational and noninvasive modulation of these weak interactions by integrating light-responsive moieties into the structure of polymer electrolytes provides an elegant way to tune the ion mobility and conductivity in situ. , Huang and co-workers reported supramolecular ion-conducting hydrogels using azobenzene to mediate reversible changes in conductivity by competitive guest–host interactions. ,, We recently developed a photoswitchable polymeric ionic liquid based on imidazolium-containing diarylethene (DAE) cations and observed that ionic conductivity can be reversibly modulated by tuning the positive charge distribution and cation–anion interaction upon light irradiation . However, current light-responsive ion-conducting polymer electrolytes have relatively poor solid-like mechanical properties, because they are either viscous liquids with a low glass-transition temperature ( T g ≪ 20 °C) or solvent-containing hydrogels. , Consequently, the materials are difficult to integrate into devices. The development of light-responsive, ion-conducting polymers that are mechanically robust, capable of self-healing, and inherently tunable remains a major challenge.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The rational and noninvasive modulation of these weak interactions by integrating light-responsive moieties into the structure of polymer electrolytes provides an elegant way to tune the ion mobility and conductivity in situ. 15,16 Huang and co-workers reported supramolecular ion-conducting hydrogels using azobenzene to mediate reversible changes in conductivity by competitive guest−host interactions. 3,17,18 We recently developed a photoswitchable polymeric ionic liquid based on imidazolium-containing diarylethene (DAE) cations and observed that ionic conductivity can be reversibly modulated by tuning the positive charge distribution and cation−anion interaction upon light irradiation.…”
Section: ■ Introductionmentioning
confidence: 99%